Analisis Penyederhanaan Verifikasi Pembayaran Donasi di Yayasan GNOTA Berbasis Sistem Otomatis Xendit - Surya, Catherine; Catherine; Syahrani Agustina; Anisa Salsabila Aprisa; Alfonsa Metafani Yaneke Massi; Ego Umarella Tofani (Jurnal Informatika & Teknologi Cerdas, 2025)
serve as the primary foundations for maintaining public trust in non-profit organizations. However, Yayasan Gerakan Nasional Orang Tua Asuh (GNOTA) currently faces significant challenges in managing fund receipts due to a manual donation verification process that necessitates the uploading of transfer proofs and visual reconciliation. This mechanism is deemed inefficient and vulnerable to recording errors (human error), manipulation risks, and confirmation delays. Consequently, this study aims to modernize this workflow by designing an automated payment verification system integrated with a third-party Payment Gateway, Xendit. The research utilizes a UML approach, encompassing Use Case Diagrams, Activity Diagrams, and Class Diagrams, to visualize the system architecture. The design results demonstrate that the proposed solution, which adopts the STP concept utilizing Virtual Account features, Dynamic QRIS, and Webhook technology, successfully transforms the transaction model into a "select-pay-complete" flow and updates payment status in real-time without manual intervention. In conclusion, the integration of this automated system proves effective in streamlining verification bureaucracy, ensuring financial data validity, and providing an instant donation experience, which is expected to enhance operational cost efficiency and strengthen Yayasan GNOTA's credibility in the digital economy era.